Food Safety Knowledge and Practice among Community in Sg. Pelek, Sepang, Selangor Darul Ehsan - Nur Ain Mahat; Chong Kok Shi; Sabariah Abd Hamid (International Journal of Public Health Science (IJPHS), 2016)
Food safety is a basic requirement of food quality. It is an increasingly important public health issue to prevent and control food borne illnesses. A cross-sectional study was designed to determine level of knowledge and practice on food safety, to determine the association between knowledge and practice, and also to identify the association between socio-demographic factors and practice score of the population studied. This study was conducted among adult population in Taman Bahagia, Sungai Pelek, Sepang, Selangor Darul Ehsan. Data were collected using an interviewed structured questionnaire. A stratified random sampling was performed to obtain houses, followed by simple random sampling to select sample in the house. A total of 115 data sets were analysed using Statistical Package for Social Sciences (SPSS) version 20.0. Analysis showed that 35% of respondents have poor level of knowledge on food safety, whereas 27% of the respondents have poor level of practices on food safety. Multiple linear regression revealed that there are a significant association between education level (p<0.001), Adj b=2.57 (95% CI: 1.15, 3.99) and gender (p=0.048), Adj b=1.15 (95% CI: 0.01, 2.29) with practice score on food safety. Therefore, health promotion and education on the importance of practicing food safety at home should be focused to prevent further unwanted health effects.